The future of Europe - Piris, Jean-Claude (Cambridge, United Kingdom Cambridge University Press, 2012)
The European Union is in crisis. Public unease with the project, Euro problems and dysfunctional institutions give rise to the real danger that the European Union will become increasing irrelevant just as its member states face more and more challenges of a globalised world. Jean-Claude Piris, a leading figure in the conception and drafting of the EU's legal structures, tackles the issues head on with a sense of urgency and with candour. The book works through the options available in light of the economic and political climate, assessing their effectiveness. By so doing, the author reaches the (for some) radical conclusion that the solution is to permit 'two-speed' development: allowing an inner core to move towards closer economic and political union, which will protect the Union as a whole. Compelling, critical and current, this book is essential reading for all those interested in the future of Europe.
Introduction <U+000d><U+000a>1 The continuing need for a strong EU in the foreseeable future <U+000d><U+000a>2 An assessment of the present situation of the EU <U+000d><U+000a>3 First option: substantially revising the EU treaties <U+000d><U+000a>4 Second option: continuing on the present path while developing further closer cooperation <U+000d><U+000a>5 Third option: politically progressing towards a two-speed Europe <U+000d><U+000a>6 Fourth option: legally building a two-speed Europe <U+000d><U+000a> Conclusion
Keywords: Unión Europea